Immune responses to highly conserved influenza A virus matrix 1 peptides. (June 2017) - Lohia, Neha; Baranwal, Manoj
ABSTRACT: Influenza vaccine development is considered to be complicated and challenging. Constantly evolving influenza viruses require continuous global monitoring and reformulation of the vaccine strains. Peptides that are conserved among different strains and subtypes of influenza A virus are strongly considered to be attractive targets for development of cross protective influenza vaccines that stimulate cellular responses. In this study, three highly conserved (>90%) matrix 1 peptides that contain multiple T cell epitopes, ILGFVFTLTVPSERGLQRRRF (PM 1), LIRHENRMVLASTTAKA (PM 2) and LQAYQKRMGVQMQR (PM 3), were assessed for their immunogenic potential in vitro by subjecting peripheral blood mononuclear cells from healthy volunteers to repetitive stimulation with these chemically synthesised peptides and measuring their IFN‐γ concentrations, proliferation by ELISA, and 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, respectively. Seven samples were screened for immunogenicity of PM 1 and PM 2, and six for that of PM 3. All six samples had positive responses (IFN‐γ secretion) to PM 3 stimulation, as did five and three for PM 2 and PM 1 respectively. In contrast, seven (PM 1 and PM 2) and four (PM 3) samples showed proliferative response as compared with unstimulated cells. The encouraging immunogenic response generated by these highly conserved matrix 1 peptides indicates they are prospective candidates for development of broadly reactive influenza vaccines.